2022
DOI: 10.23922/jarc.2021-042
|View full text |Cite
|
Sign up to set email alerts
|

A Trial Protocol of Precision Medicine for Patients with RAS Wild Metastatic Colorectal Cancer Using Liquid Biopsy (RAS-liquid Study): A Prospective, Multicenter Observational Study

Abstract: Background: Anti-epidermal growth factor receptor (EGFR) therapy has been identified to prolong the survival of metastatic colorectal cancer (mCRC) patients without RAS mutations. However, its efficacy is not always consistent for these patients. Genomic profiles of primary tumors and metastases are not always concordant; thus, chemotherapeutic agents can alter the tumor molecular profile. This molecular heterogeneity may explain resistance to anti-EGFR therapy. Liquid biopsy using circulating tumor DNA (ctDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Droplet digital PCR can offer the possibility to detect mutant DNA at allele frequencies below 0.5% 16 . Furthermore, in a recent study, the protocol involved the application of a mutation allele frequency threshold above 0.1% 17 . Considering these factors, we adapted two cut‐off values to determine RAS/BRAF mutations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet digital PCR can offer the possibility to detect mutant DNA at allele frequencies below 0.5% 16 . Furthermore, in a recent study, the protocol involved the application of a mutation allele frequency threshold above 0.1% 17 . Considering these factors, we adapted two cut‐off values to determine RAS/BRAF mutations.…”
Section: Methodsmentioning
confidence: 99%
“…16 Furthermore, in a recent study, the protocol involved the application of a mutation allele frequency threshold above 0.1%. 17 Considering these factors, we adapted two cut-off values to determine RAS/BRAF mutations. One was the conventional cut-off value for detecting RAS/BRAF mutations in formalin-fixed paraffinembedded samples (300 indexes for the majority of mutation detection beads).…”
Section: Detection Of Ras and Braf V600e Mutations In Ccfdnamentioning
confidence: 99%
“…Clinical studies are currently being conducted to standardize the frequency of sampling and interpretation of results. Two prospective studies have attempted to establish the prognostic value of liquid biopsy protocols; both studies including periodic three-monthly ctDNA analyses and clinical follow-up in CRC wt KRAS patients exposed to 5-fluorouracil regimens plus anti-EGFR antibodies[ 72 , 73 ]. Finally, current international guidelines, such as ESMO, have concluded that although there is insufficient evidence to recommend follow-up with liquid biopsy, such analysis could be useful for detecting secondary resistance to anti-EFGR[ 4 ].…”
Section: Future Perspectivesmentioning
confidence: 99%